THE DIFFICULTY OF CONTEXTUAL PROBLEM SOLVING ON FLAT BUILDINGS MATERIAL BASED ON GENDER IN FIFTH GRADE STUDENTS - Fadhilah Rimma Bestari; Sukartono (Universitas Majalengka, 2024)
Problem solving difficulty is one of the difficulties experienced by students when choosing the correct strategy to obtain an answer. In general, problem solving problems are contextual in nature that are based on student reality. The difficulty of solving contextual problems, especially in flat building material, causes math subjects to be unpopular with students. In solving contextual problem solving problems, the ability of each student will be different which can be seen from gender differences, namely men and women. The goal of this study is to characterize the disparities in fifth-grade students at Gondang 1 State Elementary School as well as the challenges that male and female students face when attempting to solve contextual problems with flat shapes. Descriptive qualitative research is employed in this kind of study. Teachers and students in the fifth grade served as the research subjects. Semi-structured interviews, documentation, and observation were the methods of data collecting that were employed. Technique and source triangulation were employed in data validity methodologies. Data reduction, data visualization, and conclusion drafting are examples of data analysis approaches. The results showed that male students had difficulty developing a problem solving plan, difficulty counting, especially multiplication and division, difficulty checking or looking back at the results of the work and they were not accustomed to writing conclusions to the problems asked in the problem. Meanwhile, female students have difficulty operating multiplication and division, are less careful in checking back the results of work and are not accustomed to writing conclusions to the problems asked in the problem. The difference in the difficulty of solving contextual problems of flat building material between male and female students lies in the second stage, namely developing a problem-solving plan and the fourth stage, namely checking or looking back.